Digital per-oral cholangioscopy to diagnose and manage biliary duct disorders: a single-center retrospective study - Robles-Medranda, Carlos; Soria-Alcívar, Miguel; Oleas, Roberto; Baquerizo-Burgos, Jorge; Puga-Tejada, Miguel; Valero, Manuel; Pitanga-Lukashok, Hannah (Endoscopy International Open, 2020)
Background and study aims Digital, per-oral cholangioscopy (POCS) allows diagnosis of biliary ducts disorders and treatment for complicated stones. We aimed to determine the diagnostic accuracy of digital POCS systems for stricture lesions and the factors precluding complete biliary stone clearance.Patients and methods We performed a retrospective analysis of a prospective database of 265 consecutive patients referred for POCS between December 2016 and July 2018. We first analyzed the diagnostic accuracy of digital POCS for malignant and benign stricture lesions in 147 patients. Then, we analyzed the factors associated with complete or partial biliary stone clearance achieved with electrohydraulic lithotripsy (EHL) delivered via POCS in 118 patients.Results In the diagnostic group, digital POCS achieved 91 % visual-impression sensitivity, 99 % specificity, 99 % positive and 91 % negative predictive values, and 63.64 positive and 0.09 negative likelihood ratios for malignancy diagnosis. In the therapeutic group, complete biliary stone clearance was achieved by EHL in 94.9 % patients; the mean stone size was 20 mm (10–40 mm). In multivariable analyses, a stone size > 20 mm (OR: 1.020, P < 0.001) and the number of stones ≥ 3 (OR: 1.276, P < 001) was associated with partial biliary stone clearance. Adverse events were reported in 3.3 % patients; no deaths were reported 30 days after the procedure.Conclusions Digital POCS has excellent diagnostic efficacy for biliary lesions. EHL via POCS is effective for complicated biliary stone clearance. Stone size (> 20 mm) and the number of stones (≥ 3) are associated with partial biliary stone clearance.